Effects of muscle-tendon mechanical properties and electromyographic activity patterns on individual differences in force-power relationship - Takehiro Kosaka; Keitaro Kubo (PLoS ONE, 2026)
This study aimed to examine the effects of muscle-tendon mechanical properties and electromyographic activity patterns on individual differences in the force-power relationship during jumping with and without countermovement. Twenty men executed unilateral jumps using only ankle joint under the following conditions: no-countermovement jump (noCMJ) and countermovement jump (CMJ) with five different loads (0, 10, 30, 50, and 70% of 1 repetition maximum (RM)). During concentric phase of each jump, mean power and electromyographic activities were measured. In addition, the power ratio of higher load conditions (50% and 70% 1RM) to lower load conditions (0% and 10% 1RM) was calculated as an indicator of individual differences in the force-power relationship. Active muscle stiffness of medial gastrocnemius muscle was calculated according to changes in estimated muscle force and fascicle length during fast stretching at three different angular velocities (100, 300, and 500 deg·s -1 ) after submaximal isometric contractions. Tendon stiffness was measured during ramp and ballistic contractions. For noCMJ and CMJ, active muscle stiffness at all angular velocities and the ratios of electromyographic activities were not significantly correlated with the power ratio. Tendon stiffness measured during ramp and ballistic contractions was significantly correlated with the power ratio for noCMJ, but not CMJ. In conclusion, individual differences in the force-power relationship during jumping without countermovement are associated with the tendon mechanical properties, whereas those with countermovement are not related to the muscle-tendon mechanical properties and electromyographic activity patterns.